Gendered participation in water management: issues from water users' associations in South Asia - Meinzen-Dick, Ruth S.; Zwarteveen, Margaret (International Food Policy Research Institute, 2003)
The devolution of natural resource management responsibility from the state to communities or local user groups has become a widespread trend that cuts across countries and resource sectors. Unlike claims to the contrary in policy narratives, devolution of control over resources from the state to local organizations does not necessarily lead to greater participation and empowerment of all stakeholders (Cleaver 1999). Because the outcome of devolution programs hinges on the activity of local organizations, this study (Meinzen-Dick and Zwarteveen 1998) examines the extent and forms of women’s participation in these organizations, using examples of water users’ associations in South Asia. This chapter tries to draw out the main issues, illustrate them with empirical examples, and examine ways to increase women’s involvement in resource management organizations.